2020
DOI: 10.1001/jamaophthalmol.2019.5413
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Central Visual Field Loss in End-stage Glaucoma by Unsupervised Artificial Intelligence

Abstract: IMPORTANCE Although the central visual field (VF) in end-stage glaucoma may substantially vary among patients, structure-function studies and quality-of-life assessments are impeded by the lack of appropriate characterization of end-stage VF loss. OBJECTIVE To provide a quantitative characterization and classification of central VF loss in end-stage glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Each total deviation (TD) plot was decomposed into 16 archetypal patterns including one normal VF pattern and 15 defect patterns determined in our prior work, 42 which were clinically validated in a subsequent study 45 and further applied to improve glaucoma diagnosis and progression detection. 39,[46][47][48] An illustration of the 16 archetype (AT) patterns and corre-sponding nomenclature can be found in Figure 1A. An example of VF decomposition into ATs is shown in Figure 1B.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Each total deviation (TD) plot was decomposed into 16 archetypal patterns including one normal VF pattern and 15 defect patterns determined in our prior work, 42 which were clinically validated in a subsequent study 45 and further applied to improve glaucoma diagnosis and progression detection. 39,[46][47][48] An illustration of the 16 archetype (AT) patterns and corre-sponding nomenclature can be found in Figure 1A. An example of VF decomposition into ATs is shown in Figure 1B.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Furthermore, artificial intelligence tools like convolutional neural networks and other deep-learning approaches have been applied to study the onset and progression of glaucoma, both structurally and functionally. 54 56 Our results suggest that substantial information about the disease onset is available before the development of functional deficits. As deep-learning approaches are specialized in exploiting such “hidden” information to classify and predict outcomes, our findings also encourage further deep-learning applications to predict the onset of future functional vision loss from retinal structure.…”
Section: Discussionmentioning
confidence: 73%
“…This approach has previously been used to classify fields in glaucoma, as well as to detect progressive change over time. [17][18][19][32][33][34][35][36] Finally, semisupervised learning uses a combination of the two approaches, where one has a relatively small set of labeled data and generally a much larger amount of unlabeled data. The labeled dataset is used to obtain a reasonable initial model, which is then used to perform predictions on the unlabeled dataset.…”
Section: Training Validation and Testing Of Deep Learning Modelsmentioning
confidence: 99%
“…The authors showed that the patterns detected by their technique, such as arcuate, partial arcuate, etc., corresponded well to classification by human graders in the Ocular Hypertension Treatment Study. In a follow-up study, Wang et al 32 proposed to use archetypal analysis to classify central visual field patterns in glaucoma. It should be noted, however, that archetypal analysis is a statistical technique closely resembling traditional factor analysis and bearing no relationship to deep learning artificial neural networks.…”
Section: Introductionmentioning
confidence: 99%